Lable-free aptamer portable colorimetric smartphone for gliadin detection in food - Qin, Yadi; Zhang, Sicheng; Qian, Jie; Meng, Fanxing; Yao, Jun; Zhang, Minwei (Frontiers in Bioengineering and Biotechnology, 2024)
For individuals with celiac disease (CD), the current clinical therapy option available is a lifelong gluten-free diet. Therefore, it is essential to swiftly and efficiently detect gluten in foods. A colorimetric sensor has been developed, which operates by regulating the aggregation and dispersion state of AuNPs induced by high concentration NaCl through the specific binding of gliadin and aptamer, thereby achieving rapid detection of gliadin in flour. It is found that the sensor exhibits good linearity in the concentration range of 0.67-10 μM and the LOD (3σ/S) is 12 nM. And it can accurately distinguish various types of free-gliadin samples, with a spiked recovery rate of 85% -122.3%. To make the detection process more convenient, the colorimetric results of the biosensor were translated into RGB color-gamut parameters by a smartphone colorpicking program for further analysis. Gliadin can still be accurately quantified with the established smartphone platform, and a correlation coefficient of 0.988 was found. The proposed portable smartphone aptamer colorimetric sensing device has achieved satisfactory results in the rapid detection of gliadin in food.